UPAYA MENCAPAI SDGs POIN KEENAM (AIR BERSIH DAN SANITASI LAYAK): PROGRAM CITARUM HARUM 2018 – 2022 DI KABUPATEN BANDUNG - Akbar, Taufan Herdansyah; Dwiyanto, Yoga (Jurnal Academia Praja, 2024)
Countries around the world have issued the Sustainable Development Goals (SDGs) for the period 2015-2030, inviting all communities worldwide to protect the earth through 17 main goals and 169 targets for sustainable development. The sixth point of the SDGs focuses on the issue of "Clean Water and Sanitation," which is the focus of this researcher's discussion, considering the condition of many Indonesian and global communities who still face significant difficulties in accessing clean water and proper sanitation. The Citarum Harum Program, launched in 2018, is one of Indonesia's efforts to accelerate the achievement of the sixth SDG, which is related to the Citarum River as one of the main sources of clean water for the surrounding communities. The results of this study show significant progress through the improvement of the water quality index in the Citarum River, increased public awareness and participation, and the relatively effective use of the pentahelix scheme. However, several evaluations are still needed for better program implementation in Bandung Regency.